Telkomsel's Orbit Product Sales Strategy Through E-Commerce at PT Akar Daya Mandiri in Gresik Regency - Khoffifah Maharani Aisya Putri (Jurnal Manajemen Bisnis dan Pariwisata, 2025)
The development of e-commerce has provided access for companies to expand their market reach and increase sales. PT Akar Daya Mandiri is an official distributor that markets various Telkomsel products, including the Orbit modem which was introduced in 2020. In the era of digital transformation and also the growth of e-commerce in Indonesia, this company began to implement a digital marketing strategy through Tiktok Shodan Shopee as a means to expand market reach. This study analyzes the success of digital marketing strategies, determines the influence of live streaming on sales, promotions through paid advertising, and evaluates visual promotions in the form of video content to increase the purchasing power of Telkomsel's Orbit products using a qualitative approach. This research is expected to contribute to the company in analyzing marketing strategies in the digital era to increase sales of Telkomsel's Orbit products.